FORECASTING THE DEGREE OF POLLUTION IN SOIL, UNDERGROUND AND SURFACE WATER SOURCES BY PESTICIDES FROM THE TRIAZOLONES, TRIKETONES AND CARBOXAMIDES CLASSES IN A WIDE RANGE IN SOIL – CLIMATIC CONDITIONS - Martіianova Yuliia; Korshun , Mariia (The Ukrainian Scientific Medical Youth Journal, 2021)
The dominant position in a battle with pests, weeds and plants’ diseases is occupied by chemical sprays, the usage of which ensures high yields of crops. However, along with high economic benefit, there is a potential risk of widespread use of pesticides due to their toxicity to living organisms, including mammals, and the ability to accumulate in soils, migrate in contacting its protection and eventually come into the body mainly with food and drinking water. The aim of our study is to hygienically assess the potential risk of soil contamination and migration in the system "soil-underground and surface water sources" of three new pesticides from different chemical classes in a wide range of soil and climatic conditions. Methods. The objects of the study were the stability, ecotoxicological hazard and migration ability of two herbicides: amicarbazone from the chemical class of triazolinone compounds and bicyclopyrone from the class of tricetones, and the fungicide pydiflumetofen from the class of carboxamide. Based on data on physicochemical properties, soil stability and toxicometry parameters, the hazard of the investigated substances in the soil-water system was assessed, the ecotoxicological hazard (ecotox) was defined; migration probability was assessed into groundwater using the organic carbon sorption constant (Kos), screening leachability index (LIX), groundwater ubiquity score (GUS) and potential contamination index for ground- and river water (LЕАСНmod). Results and discussion. It was found that pydiflumetofen is a highly resistant (I class) and low-mobility (IV class according to Kos) pesticide in soil, with a wide (from minimum to almost maximum) leaching potential according to the screening index LIX, which has from very low to high ability to leach according to GUS indices (from V to II class) and LЕАСНmod (from III to I class). Amicarbazone is a stable (II class), mobile (II class according to Kos) and washable according to LIX (practically in any soil and climatic conditions) pesticide with high (I class) according to LЕАСНmod and from low (IV class) to very high (I class) on GUS ability to leach. Bicyclopyrone - highly resistant (I class) in laboratory and stable (II class) in field experiments; Kos is from very mobile (I class) to low mobile (IV class), which led to a wide (from 0 to almost 1) leaching potential for LIX, high (I class) ability to leach according to LЕАСНmod and from very low (V class) to a very high (I class) probability of leaching by GUS. The ecotoxicological danger of the studied pesticides in different soil and under different climatic conditions is lower by 1–5 orders of magnitude in comparison with DDT; in addition, the risk of adverse effects on terrestrial biocenoses of bicyclopyrone is lower than that of amicarbazone and pydiflumetofen. Conclusion. The test substances are washable for screening index LIX and showed a high probability of dangerous pollution of surface and ground water by indexes GUS and LЕАСНmod, although in certain soil and under certain climatic conditions pydiflumetofen and bicyclopyrone inherent low amicarbazone - moderate capacity for leaching index GUS. The final assessment of the risk to human health of migration of the studied pesticides in the "soil-water" system will be provided based on the results of studies of their behavior in soil and climatic conditions of Ukraine.